Atomistic Simulation of Y-Doped [alpha]-Alumina Interfaces - Galmarini, Sandra; Aschauer, Ulrich; Bowen, Paul; Parker, Stephen C (Journal of the American Ceramic Society, 2008)
The exact mechanism of creep resistance enhancement due to yttrium (Y) doping in α-alumina is still subject to speculation, although it is known that dopants segregate strongly to grain boundaries. The current work applies atomistic simulation techniques to the study of segregation to a reasonable number of interfaces in Y-doped α-alumina. Y is shown to segregate stronger to surfaces than grain boundaries and to form ordered structures at the interfaces, which may decrease diffusion coefficients. These Y-ordered regions may act as nucleation sites for YAG precipitates particularly for rapid sintering techniques. [PUBLICATION ABSTRACT]